Freezing, pasteurizing, and drying effects on pomegranate juice flavor and acceptance - Anderson, Erika L. (Kansas State University, 2014)
Pomegranate fruits are seasonally produced and require processing to provide year round availability. Effects of processing on phenolic compounds, color, and other physical properties have been examined but few studies have examined the sensory effects. Juice prepared from fresh Wonderful pomegranates was used to prepare fresh frozen juice, batch pasteurized juice, and reconstituted juice from dried arils. These juices were evaluated using analytical and affective sensory methods to increase the understanding of processing effects on pomegranate juice properties. A modified consensus flavor profile showed that a large number of small differences existed. The accumulation of these changes demonstrates the distinction among processing methods. Time intensity multi-evaluation (TIME) profiling, a new method, was used to further understand how multiple attributes, including aromatics, feeling factors, and basic tastes, changed over the course of one sip. Fruity flavor was consistently the first to appear in the profile while bitterness and astringency lasted the longest. The attribute woody displayed longer peak times in the pasteurized and reconstituted samples than seen in fresh frozen juice. Semi-Continuous Consumption (SCC) profiling, another new method, explained product differences over 25 sips that mimicked consumption. Overall, astringent and bitter components increased while fruity and overall sweet attributes declined. These profile changes differed by sample with reconstituted juice showing the least increase in astringency over consumption. The juice samples were subjected to an acceptance test that showed four liking clusters, one that accepted all three juices and three clusters that disliked one of each juice type. The results from these studies are an initial step in describing how processing of pomegranate juice can effect flavor. Understanding the flavor differences is beneficial to processors for marketing products and for purchasers of these products for ingredient usage. Furthermore, the process of TIME and SCC profiling are described which are beneficial for understanding how multiple flavors change over single and multiple consumption events of a product respectively. These new methodologies are useful in explaining the experience of complex products such as teas and coffees or products exhibiting build-up such as nutrition aides.
Keywords: Sensory; Pomegranate juice; Flavor; Consumer acceptance; Food Science (0359)